Long-term safety of posterior chamber implantable phakic contact lens for the correction of myopia - Sachdev G (Dove Medical Press, 2019)
Gitansha Sachdev, Dandapani Ramamurthy The Eye Foundation, Coimbatore, India Purpose: To review the safety of the implantable phakic contact lens (IPCL V1, Caregroup Sight Solutions, India) for correction of myopia and myopic astigmatism. Methods: Retrospective interventional case series including 134 eyes which underwent IPCL implantation for correction of myopia and myopic astigmatism at a tertiary eye care hospital in South India. Intraoperative and postoperative complications were analyzed. The following parameters were analyzed at preoperative and 1, 6 and 12 month postoperative visits: visual acuity (in logMAR) and manifest refraction, slit lamp bio microscopy, dilated fundus examination, IOP and endothelial cell density measurement. Results: No intraoperative complications were noted. Cataract was the most common postoperative complication, wherein three eyes (2.2%) underwent observation for visually insignificant anterior subcapsular cataract and one eye (0.7%) required surgical intervention. Four eyes developed transient increased IOP due to steroid response (3 eyes) and pupillary block glaucoma (1 eye). The endothelial cell loss noted over a 1-year follow-up was 2.01%±4.12% (P=0.71). One eye developed hypopyon on the third postoperative day, which resolved subsequently with an unaided vision of 20/20. No vision threatening complications were noted. The mean follow-up in the cohort was 25.66±16.45 months. Conclusion: The IPCL is a safe and effective treatment modality for correction of myopia and myopic astigmatism. Keywords: phakic intraocular lens, implantable collamer lens, ICL, IPCL, implantable phakic contact lens, myopia, myopic astigmatism, refractive correction